Analisis Perencanaan dan Pengendalian Proyek Kapal X di PT XYZ dengan Menggunakan Metode Earn Value Management - Fredika Aura K.A; Rizqi Novitasari (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2024)
XYZ is a shipyard company in Indonesia. The company PT. However, the shipbuilding process experienced a delay in the project completion target due to the Covid-19 pandemic. In this research, it is devoted to monitoring ship projects for 30 months, so the EVM earnings value management method is needed to calculate CPI and SPI in order to get results of late calculations for the project and so that it can be re-evaluated using the EVM method, in the results of the EVM CPI and SPI method calculations occur. The delay was due to the impact of Covid-19, while for the SPI in the first 10 months the budget realization was small so it didn't require a lot of costs because the SPI result was greater than 1. However, for the CPI value of the Ship.